The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.tetlet.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthesis of 3-(substituted)pyrimido[4,5-c]pyridazine-5,7(1H,6H)-diones

Abstract: An improved synthesis of 3-(substituted)pyrimido [4,5-c]pyridazine-5,7(1H,6H)-diones, a known subclass of 4-deazatoxoflavins, is reported. The approach involves treatment of 3-methyl-6-(1-methylhydrazinyl) uracil with representative phenyl and alkyl glyoxal monohydrates, which in turn are obtained by selenium dioxide oxidation of the corresponding phenyl and alkyl methyl ketones. The first entry into 4-monosubstituted isomers is also reported. KeywordsPyrimido [4,5-c]pyridazine-57(1H6H)-dione; 4-Deazatoxoflavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Indeed, the pattern of δ (H 5 ) > δ (H 6 ) that is observed for related arylsubstituted cyanopyridazinones is consistent with the observations made by Showalter and coworkers for pyrimidopyridazine derivatives. [38] The product ratios were determined by inspection of the 1 H NMR spectra, using the intensities of the signals assigned to H 5 and H 6 of the pyridazinone rings. The yields and product ratios obtained from procedure B are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the pattern of δ (H 5 ) > δ (H 6 ) that is observed for related arylsubstituted cyanopyridazinones is consistent with the observations made by Showalter and coworkers for pyrimidopyridazine derivatives. [38] The product ratios were determined by inspection of the 1 H NMR spectra, using the intensities of the signals assigned to H 5 and H 6 of the pyridazinone rings. The yields and product ratios obtained from procedure B are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, mixtures of 5-and 6-arylcyanopyridazinones were obtained by this procedure. However, such a rationalization for the regioselectivity is shown to be oversimplistic by the observations of Showalter and coworkers, [38] who noted that in a series of arylglyoxals, the reaction of hydrazine with glyoxal carbonyls depended more on the solvent and acidity of the medium than on the electronic effects of the aryl substituent. They have also reported that in hydroxylic solvents such as water, similar to our reaction conditions, hydrazine can react with both glyoxal carbonyls and this leads to form the mixture of regioisomers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6‐(l‐Alkylhydrazino)isocytosines have been also reported to cyclize with 1,3‐diketo esters or with simple α‐keto esters to give the corresponding pyrimido[4,5‐ c ]pyridazines in good yields . Morrison and co‐workers were described the cyclizations of glyoxals with 6‐hydrazinoisocytosines while the synthesis of 3‐(substituted)pyrimido[4,5‐ c ]pyridazine‐5,7(1 H ,6 H )‐diones were performed by Turbiak through the condensation of 3‐methyl‐6‐(1‐methylhydrazinyl)uracil with phenyl and alkyl glyoxal monohydrates . A series of new 4‐aryl‐6,8‐dimethylpyrimido[4,5‐ c ]pyridazine‐5,7(6 H ,8 H )‐dione derivatives were synthesized via three component reactions of 1,3‐dimethylbarbituric acid with arylglyoxals in the presence of hydrazinium dihydrochloride .…”
Section: Introductionmentioning
confidence: 99%
“…3 A broad spectrum of biological activity have been reported for dihydropyrimidinones and pyridazine derivatives. 4 For example, the pyridazine structure found within the structure of several pharmaceutical drugs such as cadralazine, 5 minaprine, 6 cefozopran, 7 pipofezine (azaphen), The structures and purity of the obtained products were deduced from their infrared (IR), elemental analysis (CHN), and nuclear magnetic resonance (NMR) spectral data. As a suitable evidence for chemoselectivity of the reactions, the 1 H NMR (DMSO-d 6 , 400 MHz) spectrum of compound 4a exhibited two singlets of the nitrogen protons (δ = 10.61 and 10.10), a doublet (δ = 7.35) and singlet signals (δ = 7.20) corresponding to the aromatic protons.…”
Section: Introductionmentioning
confidence: 99%